The Convergence of Economic Growth: Case Study of East Java - Herman Cahyo Diartho; Rafael Purtomo Somaji; Gheghe Rizky Kharisma (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2023)
Economic growth is a parameter in achieving regional economic development, which describes an increase in the actual production capacity and the dynamics of the regional economy. This study aims to determine whether there is a yearly decrease in economic growth inequality (sigma convergence) or an acceleration of low economic growth to high economic growth (beta convergence) in East Java in 2016 – 2021. This study used secondary data. The analytical method used in this study is convergence and panel data regression analysis. The results showed that the dispersion of economic growth experienced a downward trend, indicating the occurrence of sigma convergence in East Java. Underdeveloped regions do not grow faster than developed regions, showing no absolute beta convergence in East Java. The HDI and Population Variables have not been able to accelerate convergence in East Java, indicating no conditional beta convergence in East Java.